Polyurethane/clay shape memory nanocomposites based on palm oil polyol - S.A., Zubir (2015)
Thermoplastic polyurethane (TPU) nanocomposites were prepared using polycaprolactonediol as the soft segment, 4,4'-diphenylmethane diisocyanate as the hard segment, 1,4-butanediol and palm oil polyol. Nanoclay with certain weight percent (wt%) was reinforced as filler to improve both mechanical and shape memory behavior of the nanocomposites. Palm oil polyol was introduced in order to provide hyperbranched structure for better dispersion of filler in the matrix as well as aiding the crosslinking process. The experimental results showed that the mechanical and shape memory behavior of clay reinforced polyurethane nanocomposites were influenced by clay weight percent in the polymer matrix. TPU with 3 wt% clay showed optimum values of mechanical properties while the shape memory behavior decreases with increasing clay content. © (2012) Trans Tech Publications, Switzerland.